A new method for the synthesis of nanomaterials for the needs of nanotechnologies - Korduban, O.M.; Kryshchuk, T.V.; Medvedskij, M.M. (Reports of the National Academy of Sciences of Ukraine, 2021)
A new method for the synthesis of nanomaterials using the an electric explosion of wires (EEW) has been developed. In it, the process of nanopowder synthesis is combined in time with other syntheses in order to use EEW nanopowders as superactive precursors of real-time reactions. For the first time, new types of catalytic plasma nanocoatings WO3–x/stainless steel were obtained directly from nanopowders. steel and mesoporous photo- and electrocatalytic nanodisperse films TiO2–x, TiO2–x/Ag. In nanomaterials of a new type, the nanodisperse structure is completely preserved, and organic components are not used in their production. Due to the use of EEW of WO3–x nanopowders as superactive precursors, the reaction temperature of the WS2 synthesis WО3–х + 3H2S → WS2 + S + 3H2O was reduced from 800 to 450 °С. It is shown that the proposed method of synthesis of nanomaterials is a new tool for solving the problems in the field of nanotechnologies.